Multiple antiarrhythmic transplacental treatments for fetal supraventricular tachyarrhythmia: A protocol for systematic review and meta analysis. Issue 50 (11th December 2020) - Chen, Tingting; Yang, Yanfeng; Shi, Kun; Pan, Yue; Wei, Sumei; Yang, Zexuan; Yang, Xiao
Abstract: Background: Fetal supraventricular tachyarrhythmia is a common reason for referral to fetal cardiology. Multiple antiarrhythmic transplacental medications can be used to treat these diseases. Debates remain regarding the standardized therapy. Methods: PubMed, EMBASE, Cochrane Library, Web of Science, Google Scholar, and ClinicalTrials.gov will be searched from inception to September 2020. A handsearching for gray literature, including unpublished conference articles, will be performed. The randomized control trials, case–control, and cohort studies will be accepted, no matter what the languages they were reported. We will first focus on the effectiveness of the therapy on fetal cardiac rhythm and/or heart rate. Then we will do further analysis of preterm delivery, fetal hydrops, intrauterine fetal demise, and maternal side effects. The Cochrane Risk of Bias Tool and the Newcastle–Ottawa scale will be used to assess the risk of bias of the randomized controlled trials, case–control, and cohort studies, respectively. Two independent reviewers will carry out literature identification, data collection, and study quality assessment. Discrepancies will be resolved by a third reviewer. Statistical analysis will be conducted using the STATA 13.0 software. Result: The results will provide helpful information about the effect of multiple antiarrhythmic transplacental therapies in pregnancies with supraventricular tachycardia or atrial flutter, and demonstrate which therapy is more effective. Conclusion: The conclusion drawn from this systematic review will benefit the patients with fetal supraventricular tachyarrhythmia.